(أعمال البعثة السورية في المدينة البيزنطية(تل الكسرة الأثري - Dahham, Yaarob (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Site, location and date: Tell el-Kisra is located to the northwest of the city of Deirez-Zor, ca. 40km on the left bank of the Euphrates. The ancient name of this site is still unknown, but A. Poidebard mentions its name as Alaan. The size of this city 27 ha, and the discovery of the defense wall and the civil construction of the site led us to believe that this site is an ancient city (polis). It is possible that Tell Kisra was an important site because of Emperor Justinian’s policy of taking responsibility for the restructuring of the military units in the region. He gave great significance to the fortification of the suburban cities of Mesopotamia. Therefore the site must be viewed in its historical content and in terms of several changes, starting from the 5th century to the beginning of the Islamic period.